FAMOUS CASES FROM AMERICAN LAW INVOLVING THE IMPLANTATION OF FALSE MEMORIES IN INDIVIDUALS WITH HIGH SUSCEPTIBILITY (PAUL INGRAM CASE) - Abhishek Kumar Amit (International Journal of Multidisciplinary Research and Studies, 2021)
To this day, all of the research has been solely concentrated on the implantation of false memories for individual occurrences. The current experiment is the first proof of concept that false memories may be implanted utilising a modified false memory implantation paradigm for repeated autobiographical events. The experiment was carried out on a human subject. In comparison to the traditional way of implanting false memories for single occurrences, we hypothesised that false memories would be generated using false memory implantation techniques for repeated events to a lesser extent. Within the context of our research, we divided our participants into one of three implantation conditions: standard, repeated, or gradual. The participants were subjected to three separate interview sessions, with a one-week break in between each session. In the Standard condition, we presented participants with a single-event implantation strategy across all three interviews. This was done to control for any potential bias.